Why go to University? Forming academic friendships at Tyndale University, a private Christian university in Ontario, Canada - Green, Beth (Religious Studies and Theology, 2023)
This paper considers why Christian Higher Education could offer a hopeful, if metaphysical, answer to the question, “Why go to university”? The paper draws on two examples to argue that a greater diversity of higher education institutions in Ontario would tell a bigger story about what going to university is for. The first example is historic and introduces four female philosophers whose academic friendship impacted postwar moral philosophy in Britain and North America. The second example is contemporary: Tyndale University is a private Christian university in Toronto. The paper argues that Tyndale University is an example of the kind of small to mid-size universities capable of fostering the academic friendships necessary to preserve diversity, resilience and alternate imaginations during times of global disruption.